COMMUNITY PREFERENCES FOR OPEN SPACE IN TANJUNGSARI â€œKOPRIâ€ HOUSING, PEKALONGAN DISTRICT - Maruf, Muhammad Imam; Indrosaptono, Djoko (Jurnal Arsitektur ARCADE, 2023)
Abstract: The purpose of this study is to examine the pattern of use of open space in Tanjungsari housing; tanjungsari kopri housing is one of the housing in Pekalongan regency in which there are three open spaces. In its development in residential areas it grows more densely. Because each resident has their own preference for the model of house construction, resulting in narrower open space, it is a concern for the author to be able to identify patterns of use of open space in tanjugsari housing.This research uses descriptive-qualitative methods with behavioral setting theory approaches. For data collection, the user conducts location surveys, interviews, documenting locations. The results of this study found that the pattern of utilization of citizens in open spaces is based on the needs and goals according to the preferences of each resident. So that the results of this study are realized in the form of sketches or diagrams in an area that is often used for activities by residents. The authors obtained data that residential communities are more dominant in outdoor activities complete with several facilities such as: seating, sports facilities, relaxing places by looking at the view of the Park and other public facilities, rather than being in open spaces with no facilities.Keywords: preference, open space, housingAbstrak: Abstract: The purpose of this study is to examine the pattern of use of open space in Tanjungsari housing; tanjungsari kopri housing is one of the housing in Pekalongan regency in which there are three open spaces. In its development in residential areas it grows more densely. Because each resident has their own preference for the model of house construction, resulting in narrower open space, it is a concern for the author to be able to identify patterns of use of open space in tanjugsari housing.This research uses descriptive-qualitative methods with behavioral setting theory approaches. For data collection, the user conducts location surveys, interviews, documenting locations. The results of this study found that the pattern of utilization of citizens in open spaces is based on the needs and goals according to the preferences of each resident. So that the results of this study are realized in the form of sketches or diagrams in an area that is often used for activities by residents. The authors obtained data that residential communities are more dominant in outdoor activities complete with several facilities such as: seating, sports facilities, relaxing places by looking at the view of the Park and other public facilities, rather than being in open spaces with no facilities.Keywords: preference, open space, housing